Mental Value Added and Sharia Value Added: Phenomenological Reflection of the Meaning of Zakat as Altruistic Behavior - Sultan; Sahrir; Darwis; Syarifuddin (LP2M IAIN Palopo, 2025)
This study aims to deeply uncover the meaning of zakat for companies, particularly in the context of zakat as mental value added and as part of the Sharia Value Added (SVA) concept. Departing from an interpretive paradigm with a phenomenological approach, this study examines how business actors interpret zakat not only as a sharia obligation, but also as altruistic behavior that contributes to mental, spiritual, and social well-being. Data were obtained through in-depth interviews, observations, and documentation of company leaders and employees who consistently pay zakat. The results show that zakat is interpreted as a voluntary act of helping others, which brings a sense of joy, pride, and satisfaction to those who do it. Informants feel that zakat functions not only as a distribution of wealth, but also as a means of purifying the soul, strengthening humanitarian values, and forming inner peace. This sense of satisfaction arises from the awareness that some of the wealth owned is the right of others.